Patterns of cesarean birth among women living with HIV in Ontario: A cross‐sectional, population‐level study. Issue 3 (17th March 2021) - Shoemaker, Esther S.; Saiyin, Tana; Smith, Stephanie; Loutfy, Mona; Darling, Liz; Walker, Mark; Hawken, Steven; Begum, Jahanara; Bibeau, Christine; Bertozzi, Breklyn; Fraleigh, Annette; Kwaramba, Gladys; et al.
Abstract: Background: In Canada, as is found globally, women of reproductive age are a growing demographic of persons living with HIV. Combination antiretroviral therapy (cART) treatment enables women living with HIV (WLWH) to become pregnant without perinatal transmission, and they are increasingly planning to become pregnant. Since 2014, Canadian guidelines no longer recommend routine elective cesarean birth (CB) for women who are virally suppressed and receiving cART. It is unknown whether their obstetric care has changed since this update. Our objective was to describe trends in cesarean births among WLWH in Ontario, Canada, over a 12‐year period. Methods: Our research is co‐led and codesigned with WLWH. We conducted a retrospective population‐level cohort study using linked health administrative databases at ICES (formally, the Institute for Clinical and Evaluative Sciences). Participants were all women who gave birth in Ontario, between 2006/07 and 2017/18. We assessed their intrapartum characteristics and used multivariable regression to determine an association between HIV status and CB, controlling for sociodemographic and clinical variables. Results: Since 2014, the overall proportion of CB among WLWH remained stable and was higher than among women without HIV (39.9% vs 29.0%, P  < 0.001). In addition, the proportion of primary CB decreased between 2006 and 2010 and between 2014 and 2018 (28.5%‐19.3%), whereas the proportion of repeat CB increased (13.1%‐20.5%, P  = 0.013). Conclusions: Because of decreasing HIV‐related indications for CB, more practitioners may be following the guidelines for first‐time mothers. Currently, no guidelines exist for care of WLWH with a previous CB, and opportunities for vaginal birth may be missed in this population.